ANALYSIS OF FACTOR FACTORS AFFECTING THE ENTREPRENEURSHIP (ENTREPRENEURIAL INTENTION) STUDY ON MEDIUM SMALL INDUSTRIES IN THE COASTAL VILLAGE OF TABANAN - I Dewa Nyoman Usadha; Ni Luh Ayu Suda Sucandrawati (AIBPM Publisher, 2019)
Bali is famous for cultural tourism, guests visiting Bali throughout the year show an increasing trend. Conditions triggered the community to build business ventures in the tourist village area. The study was carried out in the coastal village area of Tababan district, Bali. The study population is the Small and Medium Industry (IKM) actors covering three sub-districts of Kediri, Tabanan District and Kerambitan District. Respondents in this study were selected using purposive sampling. The sample criteria are small and medium industries (IKM) with a five-year business activity period. From this study the results obtained are (1) socio-demographic factor factors such as age and education do not significantly influence Entrepreneurial intention (2) Attitudes, economic opport and ovoid respobility factors have a significant effect on entrepreneurial intentions and (3) Contextual factors namely social support, education and training proved to have a significant and positive effect. towards entrepreneurial intentions.